Applicability of technical biopolymers as absorber materials in solar thermal collectors. (1st September 2017) - Klein, Andrea; Oreski, Gernot; Resch-Fauster, Katharina
Graphical abstract: Highlights: Promising technical biopolymers as solar absorber materials are nominated. Candidate materials are CA, CAB, bio-PA, PLA, PBS. Nominees are exposed to application-relevant conditions. Aging behaviour and application-relevant properties are characterized. The potential of technical biopolymers in solar energy is evaluated as high. Abstract: A broad spectrum of commercially available technical biopolymers is screened with respect to applicability as absorber materials in solar collectors. Technical biopolymers nominated as potentially suitable (bio-polyamide, poly(lactic acid), cellulose acetate, cellulose acetate butyrate, poly(trimethylene terephthalate)) are characterized in detail and in particular with regards to their application relevant aging behaviour. Candidate materials are subjected to various exposure conditions (in water at 35 °C and 80 °C, in air at 60 °C, 70 °C and 80 °C and to the Xenontest – depending on potential collector type) for up to 1000 h. Continuously both application relevant and aging-indicative properties such as thermal, mechanical and morphological characteristics are analysed. Consequently property changes and underlying aging mechanisms are discussed. Based on these results potential application opportunities of the materials are considered. Concisely, the study reveals a high potential of technical biopolymers for solar thermal applications.